The kynurenine pathway as a potential link between ethanol-induced behavioral alterations and neuroinflammation - Gil de Biedma-Elduayen, Leticia; Giménez-Gómez, Pablo; Morales-Puerto, Nuria; Vidal, Rebeca; Del Río-García, Álvaro; Núñez-de la Calle, Carlos; Careaga, Lluna; Gutiérrez-López, María Dolores; O’Shea, Esther; Colado, María Isabel (Frontiers in Pharmacology, 2025)
IntroductionThe neuroimmune actions of ethanol have recently gained significant attention. Concurrently, the kynurenine pathway, the main catabolic route of tryptophan (TRP), has emerged as a novel target for modulating drug abuse and as a critical immune regulator. This pathway is implicated in behavioral and cognitive alterations, including anxiety, depression, and memory impairment—conditions closely associated with ethanol (EtOH) dependence. The kynurenine pathway is activated under inflammatory and immune conditions.ObjectiveWe previously demonstrated that chronic EtOH consumption increases kynurenine (KYN) levels in mice. Here, we investigate the effect of EtOH dependence and withdrawal on behavioral and cognitive parameters, the nucleus accumbens (NAc) transcriptome, and KYN, TRP and serotonin (5-HT) levels and KYN/TRP and 5-HT/TRP ratios in mice.MethodsAdult male mice were subjected the Chronic Intermittent ethanol (CIE) paradigm, a model for dependence and withdrawal. Twenty-four hours post-EtOH exposure, we analyzed behavioral and cognitive parameters, sequenced the NAc transcriptome, and measured KYN, TRP and 5-HT levels as well as KYN/TRP and 5-HT/TRP ratios in plasma, limbic forebrain, cortex and cerebellum using HPLC.ResultsThe CIE model induced anxiety-like behavior and memory impairment. Transcriptomic analysis of the NAc revealed immune system activation, including upregulation of immune and inflammation-related genes. Furthermore, chronic EtOH exposure increased KYN levels and the KYN/TRP ratio across plasma and brain regions.ConclusionThis study suggests that chronic EtOH exposure induces neuroimmune activation, which may trigger KYN pathway activation and contribute to anxiety and memory deficits observed in the CIE model.